RITUAL, SYMBOLISM, AND SPIRITUAL RESONANCE: THE XIANGXI MIAO DRUM DANCE IN THE CONTEXT OF CULTURAL PHILOSOPHY AND RELIGIOUS PRACTICE - Yang, Liu (European journal for philosophy of religion, 2025)
This study examines the formation and development of the Xiangxi Miao Drum Dance (XMDD) through a philosophical and religious lens, situating its evolution within the broader discourse of cultural ecology and spiritual practice. The research seeks to uncover how the interplay between the Miao people's ancestral environment, cosmological beliefs, and socio-cultural traditions has shaped this unique ritualistic art form. Employing a qualitative research design, the study integrates ethnographic methods—including participant observation, interviews with local practitioners, and analysis of historical texts—to explore the sacred and symbolic dimensions of XMDD. Key findings reveal that the dance originates from agricultural rituals and clan-based, matriarchal structures of Miao society, dating back to the Zhou and Qin dynasties. More significantly, the research highlights how XMDD functions as a conduit for spiritual expression, invoking divine protection, ancestral reverence, and cosmic harmony. Over time, this ritual dance has transformed from a sacred communal practice into a performative cultural heritage, yet it continues to carry profound religious and philosophical significance. The study underscores the necessity of preserving XMDD within both traditional and contemporary contexts, not merely as an artistic expression but as a vehicle for transmitting religious worldviews and philosophical reflections on identity, harmony, and transcendence. Future research should further investigate the dance’s role in shaping Miao religious thought, its contribution to interethnic philosophical discourse, and its pedagogical potential in fostering spiritual and cultural awareness.